ANALISIS PELAKSANAAN KEWAJIBAN PAJAK PERTAMBAHAN NILAI PADA PT. PANAHMAS DWITAMA DISTRINDO - Hidayatul Fauzia; Moh. Agung Surianto (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
One form of levy imposed in Indonesian legislation is the Value Added Tax (VAT) which is regulated in Law no. 42 of 2009. PT Panahmas Dwitama Distrindo Jember is a company registered as a taxpayer entrepreneur. This company is engaged in the distribution of goods from various multinational manufacturing companies since 1997. In terms of its business activities, PT Panahmas Dwitama Distrindo Jember conducts trading activities subject to VAT. The purpose of this research will be to analyze the implementation of reporting, calculating, and paying VAT carried out by PT Panahmas Dwitama Distrindo whether it is correct and appropriate or not appropriate or appropriate according to the laws and regulations. This study used a qualitative descriptive method. The data sources used in this study are input tax and output tax data in 2020. Meanwhile, the data collection methods used are interviews and documentation. The results of the study found that the implementation of Value Added Tax at PT. Panahmas Dwitama Distrindo has complied with the prevailing laws and regulations. Among them are the determination of the tax base based on the selling price, as well as the tax rate imposed at 10% of the tax base.